1999
DOI: 10.1080/000163599429020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of professional flossing with NaF or SnF2gel on approximal caries in 13-16-year-old schoolchildren

Abstract: The aim of this study was to evaluate the effect of professional flossing with NaF and SnF2 gels on caries development on approximal tooth surfaces. Two-hundred-and-eighty 13-year-old schoolchildren were divided into 3 groups: (1) NaF (n = 97), (2) SnF2 (n = 85), and (3) placebo gel group (n = 98). The investigation was carried out double-blind. The children were treated 4 times a year for 3 years with 1% NaF gel, 1% SnF2 gel, or placebo gel. The treatment was carried out by dental nurses and the time required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…7 Twenty-five trials were included, conducted between 1964 and 1996 (only five during the 1980s and one in the 1990s). Twelve trials were conducted in the United States, [26][27][28][29][30][31][32][33][34][35][36][37] four in Europe, [38][39][40] four in Brazil, [41][42][43][44] and one in each of the following countries: UK, 45 Canada, 46 Israel, 47 Hawaii, 48 and Venezuela. 49 The study conducted by Marthaler 38 was treated as two independent trials because the results for the two age groups involved were reported separately as distinct studies.…”
Section: Resultsmentioning
confidence: 99%
“…7 Twenty-five trials were included, conducted between 1964 and 1996 (only five during the 1980s and one in the 1990s). Twelve trials were conducted in the United States, [26][27][28][29][30][31][32][33][34][35][36][37] four in Europe, [38][39][40] four in Brazil, [41][42][43][44] and one in each of the following countries: UK, 45 Canada, 46 Israel, 47 Hawaii, 48 and Venezuela. 49 The study conducted by Marthaler 38 was treated as two independent trials because the results for the two age groups involved were reported separately as distinct studies.…”
Section: Resultsmentioning
confidence: 99%
“…Across all KQs, 3 systematic reviews (total of 20 684 participants) of 54 unique trials (53 publications) and 23 additional studies (in 27 publications; total of 15 026 participants) were included (Figure 3). One study assessed diagnostic accuracy of screening; the systematic reviews and other 22 studies (19 randomized clinical trials and 3 nonrandomized trials) addressed preventive interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Only 1 trial was assessed as low risk of bias. 44 Methodological limitations in the other trials included use of a quasirandomized design (7 trials), 21,22,29,[31][32][33]38 unclear randomization or allocation concealment methods (19 trials), open-label design (10 trials), and high attrition (14 trials).…”
Section: Fluoride Gelmentioning
confidence: 99%
“…NaF gels have previously been found to be able to remineralize demineralized enamel in vitro and in situ [Sawyer and Donly, 2004]. Professional flossing with NaF gel in schoolchildren has also been found to be beneficial when it comes to reducing approximal caries [Gisselson et al, 1999].…”
Section: Discussionmentioning
confidence: 98%